Short- and long-term effects of copper on anammox under gradually increased copper concentrations - MERTOĞLU, BÜLENT; KALKAN AKTAN, ÇİĞDEM; BAKIRCI, KOZET (SPRINGER, 2021)
This study aims to determine both short- and long-term response of enriched anammox culture to Cu. Assessment of short-term inhibition is based both on total applied Cu concentration and potential bioavailable fractions like intracellular, surface-bound, soluble and free Cu ion. The half maximal inhibitory concentration (IC50) values for total applied, soluble, intracellular and cell-associated concentrations were determined as 4.57 mg/L, 1.97 mg/L, 0.71 mg/L, 1.11 mg/L, respectively. Correlation between the surface-bound fraction of Cu and inhibition response was weak, suggesting that Cu sorbed to biomass was not directly responsible for the effects on anammox activity. There was a disparity between the results of short- and long-term experiments in terms of inhibition threshold concentration (i.e. short-term IC50 = 4.57 mg/L vs long-term IC50 = 6.74 mg/L). Candidatus Kuenenia (59.8%) and Candidatus Brocadia (40.2%) were the two main anammox genera within the initial biomass sample. One of the most interesting finding of the study is the demonstration that a complete wash-out of C. Brocadia genus at an applied Cu concentration of 6.5 mg/L. This strongly indicates that C. Brocadia were not able to tolerate high copper concentrations and all nitrogen conversion was carried out by C. Kuenenia during the Cu exposure period.
Keywords: Anammox; Copper inhibition; Long-term inhibition; Next-generation sequencing